Variation in adverse drug events of opioids in the United States - Liu, Edward Y.; McCall, Kenneth L.; Piper, Brian J. (Frontiers in Pharmacology, 2023)
Background: The United States (US) ranks high nationally in opioid consumption. The ongoing increases in misuse and mortality amid the opioid epidemic has been contributing to its rising cost. The worsening health and economic impact of opioid use disorder in the US warrants further attention. We therefore assessed commonly prescribed opioids to determine which ones were overrepresented versus underrepresented for Adverse Drug Events (ADEs) to better understand their distribution patterns using the Food and Drug Administration’s Adverse Event Reporting System (FAERS) while correcting for distribution using the Drug Enforcement Administration’s Automation of Reports and Consolidated Orders System (ARCOS). Comparing the ratio of the percent of adverse drug events as reported to FAERS relative to the percent of distribution as reported to the ARCOS database is a novel approach to evaluating post-marking safety surveillance and may inform healthcare policies and providers to better regulate the use of these opioids. Methods: We analyzed the adverse events for eleven prescription opioids when correcting for distribution, and their ratios for three periods: 2006-2010, 2011-2016, and 2017-2021 in the US. The opioids include buprenorphine, codeine, fentanyl, hydrocodone, hydromorphone, meperidine, methadone, morphine, oxycodone, oxymorphone, and tapentadol. Oral morphine milligram equivalents (MMEs) were calculated by conversion relative to morphine. The relative ADEs of select opioids, opioid distribution, and the ADEs relative distribution ratios were analyzed for the eleven opioids. Results: Oxycodone, fentanyl, and morphine accounted for over half of the total number of ADEs (N=667,969), while meperidine made up less than one percent. The opioid distributions were relatively constant over time with methadone repeatedly accounting for the largest proportions. Many ADEs to opioid distribution ratios increased over time, with meperidine (60.6), oxymorphone (11.1), tapentadol (10.3), and hydromorphone (7.9) most over-represented for ADEs in the most recent period. Methadone was under-represented (< 0.20) in all three periods. Conclusion: The use of FAERS with ARCOS provides insights into dynamic changes in ADEs in the US of select opioids. There is further need to monitor and address the ADEs of these drugs.